E-090 Feasibility of a Vascular Replicator for Endovascular Procedure Rehearsal. (29th July 2016) - Nickele, C; Hoit, D; Elijovich, L; Arthur, A
Abstract : Background: Multiple studies have shown the benefit of simulator use for medical trainees. In the endovascular realm, this has been demonstrated in the cardiac, vascular and neurovascular literature with both computer simulation models and physical models of the vasculature. In this study, the authors investigate the feasibility of a customized 3D model, not for training purposes, but for rehearsal prior to an actual endovascular treatment procedure. Methods: Thirty-five patients with intracerebral aneurysms in various locations were enrolled in the study. Cases were chosen based on attending surgeon preference. Rotational 3D imaging studies of the pertinent vascular distribution were used to manufacture a 3D vascular model of that patient's vascular tree. Then, prior to the actual procedure, the attending neurointerventionalist performed a practice procedure on the 3D flow model. The model was used in conjunction with a complete system containing a biphasic pump to simulate the cardiac cycle and blood flow (Vascular Simulations, Stony Brook, USA). This was a full procedure, done as the treatment procedure would be, using research materials, and a complete neuroangiography system. After the actual treatment procedure, comments were recorded from the neurointerventionalist regarding the potential benefit of the practice session. Results: Thirty-six procedures were done in thirty-five patients, 28 of the replicator sessions proved to be useful. Eight patients had replicator sessions that were not useful, and all of these were due to some failure of the replicated model. Models leaked in 4 cases, key vessels were not patent in the model in 4 cases, and 3 models had anatomic inaccuracies. When useful, the replicator sessions showed varying types of utility; allowing the operator to properly size a device, helping to choose the best wire and catheter combination to select a distal vessel, helping to understand the best landing zone for a stent, or simply allowing the operator to practice the procedure before the official treatment. Discussion: It is reasonable to think that any chance to practice a procedure prior to the final attempt at treatment would be beneficial to the physician and, by extension, the patient. This study shows that replicator practice sessions are feasible as long as the replicator model is a functional and faithful representation of the patient's vasculature. In many cases, the replicator session provided an opportunity to correctly size the endovascular device, and avoid resheathing these devices in the patient's intracranial vasculature during the actual procedure. This has the potential to reduce operative time and lower the risk of complications. But the benefits are not limited to properly sizing implants. Even just a chance to rehearse the maneuvers of a procedure benefit the patient in terms of helping to avoid difficulty during the treatment procedure. Conclusion: Difficult endovascular cases, or cases in which a new technology is being used, benefit from a practice session with an individualized 3D model, created to represent the patient's intracranial vasculature. This holds true only when the 3D model is a functional and accurate reflection of the individual's anatomy. Disclosures: C. Nickele: None. D. Hoit: 1; C; SIemens. 2; C; Siemens, Medtronic, Sequent. L. Elijovich: 1; C; Siemens, Baptist Clinic Research Institute. 2; C; Stryker, Penumbra, Microvention, Covidien. A. Arthur: 1; C; Penumbra, Sequent, Siemens. 2; C; Medtronic, Microvention, Penumbra, Sequent, Siemens, Stryker.